2009
DOI: 10.1007/bf03086209
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance, angiographic characteristics, and short-term outcomes in 30 patients with early coronary artery graft failure

Abstract: Clinical significance, angiographic characteristics, and short-term outcomes in 30 patients with early coronary artery graft failureBackground. Despite technical advances in coronary artery bypass grafting (CABG), early postoperative myocardial ischaemia still remains a challenging problem. The aim of this study was to determine the incidence, clinical features, angiographic characteristics, and management of early graft failure in the present CABG era.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…It is not clear, however, what the clinical implications of asymptomatic graft failure are, as data from trials in which angiography is incorporated into the study protocol may demonstrate twice as much graft failure as that seen in angiography for symptoms [ 18 ]. The management of asymptomatic graft stenosis or occlusion remains contentious as graft PCI and re-do CABG carry higher risk burdens [ 19 ]. Conversely, progression of atherosclerosis in saphenous grafts is associated with increased risk for subsequent coronary events independent of symptoms [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is not clear, however, what the clinical implications of asymptomatic graft failure are, as data from trials in which angiography is incorporated into the study protocol may demonstrate twice as much graft failure as that seen in angiography for symptoms [ 18 ]. The management of asymptomatic graft stenosis or occlusion remains contentious as graft PCI and re-do CABG carry higher risk burdens [ 19 ]. Conversely, progression of atherosclerosis in saphenous grafts is associated with increased risk for subsequent coronary events independent of symptoms [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…This includes new native coronary artery problems (ie, plaque rupture, thrombus), distal coronary microembolism, incomplete myocardial revascularization, inadequate myocardial protection, hypercoagulability, and preoperative severe ischemic injury. 4,7,9,11,16,19,20 In a prospective angiographic study of 1604 consecutive patients who underwent off-pump CABG, incomplete revascularization was reported in 13% and was associated with lower 5-year survival (75% vs 85%). 32 Notably, the incidence of nongraft-related causes of PMI is higher in patients undergoing combined surgical procedures where new native coronary artery occlusion was found in 20% and coronary artery spasm in 13% (5/40) of patients.…”
Section: Causes Of Perioperative Myocardial Ischemiamentioning
confidence: 99%
“…53 When anastomotic stenosis is identified, the culprit bypass graft is commonly the primary PCI target (although caution should be exercised when performing PCI on a recent anastomosis). 4,11 In cases of detected graft spasm during angiography, a catheter intervention with intragraft nitroglycerin injection can also be performed. 12 Recent guidelines recommend that redo CABG should be considered if the anatomy is unsuitable for PCI, if several important grafts are occluded, or in the case of obvious technical errors.…”
Section: Treatment Optionsmentioning
confidence: 99%
“…Both registries showed that patients with graft failure can undergo PCI with a relatively low risk for in-hospital mortality or nonfatal major complications. [143,144] SVG failure -Recurrent angina after the first few months after CABG is caused by both graft disease and by progression of atherosclerosis in non-bypassed vessels. Percutaneous intervention in SVG lesions was evaluated in several randomized studies.…”
Section: Percutaneous Coronary Interventionmentioning
confidence: 99%